Pyrimethamine toxicosis in horses given a compounded medication. (4th September 2017) - MacKay, R.; McLellan, J.; Mallicote, M.
Summary: Eight Thoroughbred horses in race training began convulsing within 24 h of dosing with a compounded medication containing toltrazuril and pyrimethamine (PYR); seizures were generalised and multiple in six of the horses. One horse died within 2 h of onset and another persistently recumbent horse was subjected to euthanasia 3 days later. Neurological signs resolved within 4 days of dosing in the remaining six horses but hyperthermia, neutropenia, oral mucositis and alopecia developed in four horses beginning on Day 6. After treatment with folinic acid and folic acid for presumptive PYR‐induced folate deficiency these signs resolved within 3 weeks. One horse developed laminitis and was ultimately subjected to euthanasia >2 months after dosing. The remaining five horses recovered and were discharged. Laboratory analysis of the suspect medication revealed that the concentrations of the two ingredients had accidentally been switched during formulation by the compounding pharmacy so that the PYR concentration was 405 g/L rather than the intended 17 g/L. This incident highlights the need for caution when using compounded preparations of potentially toxic drugs.